Rate and duration of siliqua and seed-filling period and their relation to seed yield in Brassica species - NANDA, R; BHARGAVA, S C; TOMAR, D P S (The Indian Journal of Agricultural Sciences, 2013)
The rate and duration of siliqua and seed-filling period were studied fOT different Brassica species differing in flowering behaviour under field condition. 'Varuna' indian mustard [Brassica juncea (L.) Czernj. & Cosson]. 'Pusa Kalyani' brown sarson [8. rapa (L.) Thell. emend. Metzger var ulti (prain)Schulz., syn B. campestris L. ssp oleifera (Metzger) Sinsk. var brown sarson], 'BO 706' rapeseed (B. napus L.) and 'Tall 1' ethiopian mustard (B. carinata A. Braun ) were sown in 2 different seasons during 13 October-12 December at an interval of 10 days. 'The rate of dry-matter accumulation and duration of siliqua and seed-filling period decreased with delay in sowing. The actual and effective filling periods of siliqua were correlated with yield. The predicted data indicated shortening of 1.8,4.6 and 1.3 days in actual filling period. effective filling period and seeds/siliqua respectively for every unit increase in mean temperature during 13 October-24 December. The actual and effective filling periods of siliqua increased by 4-5 daysfor every 1 hr increase in photoperiod above its mean value of 10.7-12.8 hr/day.